Combination of dynamic and kinematic vector perturbations of beams - A. M. Kaziev; Z. R. Likhov; A. Ya. Dzhankulaev; I. Yu. Kumyshev; G. A. Shigalugov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The aim of the study is to study the operation of beams under the simultaneous influence of combined actions: moments at the ends, kinematic harmonic displacements of both supports, a distributed load with different amplitudes, frequencies, phases, and the presence of viscous friction.Method. The study is based on solving a boundary value problem and modeling.Result. Investigated the forced transverse vibrations of beams with constant cross-subject to damping. Considered non-periodic, periodic and harmonic oscillations of the beams from vector perturbations. Examples of solutions for various conditions bearings beams.Conclusion. The author's development can be adapted to vibrations of bars of variable cross section, to vibrations of continuous-discrete bars. The resulting transfer functions make it possible to calculate building elements in the form of rods for random processes, taking into account their correlation.